The Influences of Stirring and Cow Manure Added on Biogas Production From Vegetable Waste Using Anaerobic Digester. (March 2018) - Abdullah, N O; Pandebesie, E S
Abstract: Based on Indonesian Government Regulation number 18, 2008, solid waste management should be conducted from the source to minimize the amount of waste. The process includes the waste from domestic, commercial, and institution. This also includes in 3R program (reduce, reuse, and recycle). Vegetable waste from market is a potential material to produce biogas due to its chemical composition (hemi-cellulose, cellulose, and lignin) which transform the biomass to be the raw material of biogas. Acid substance of vegetable becomes an obstacle in process of producing biogas. There has to be buffer material which can improve the performance of biogas process. Cow manure is a material which can be easily obtained as buffer . This research used 24 biogas reactor in volume 6 L by batch method. Biogas volume is measured by checking the preferment in manometer. Methane measurement is conducted by using Gas Chromatography (GC) Hewlett Packard (HP-series 6890) in day 15 and 30. The research was started by sample characterization, sample test by total solid analysis, volatile solid, lignin, ratio C/N, ammonium, and ash. Analysis of pH, temperature, and biogas volume is conducted every day.